2017
DOI: 10.3201/eid2304.161692
|View full text |Cite|
|
Sign up to set email alerts
|

Presence and Persistence of Zika Virus RNA in Semen, United Kingdom, 2016

Abstract: Zika virus RNA has been detected in semen collected several months after onset of symptoms of infection. Given the potential for sexual transmission of Zika virus and for serious fetal abnormalities resulting from infection during pregnancy, information regarding the persistence of Zika virus in semen is critical for advancing our understanding of potential risks. We tested serial semen samples from symptomatic male patients in the United Kingdom who had a diagnosis of imported Zika virus infection. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 32 publications
(44 reference statements)
1
67
3
3
Order By: Relevance
“…Another important factor in the determination of the long term dynamics of Zika in a population is the parameter K L which represents how well men is capable of sexually transmitting ZIKV after the viremic period ( figure 3), when compared to during it. It has been confirmed that some men can test positive for ZIKV RNA in the semen months after the viremic period 22,23 . Our model shows that until we can properly measure or estimate the sexual transmissibilities between humans in post-viremic stage, we must be prudent 24 and recommend protected sex to men returning from endemic areas with or without symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…Another important factor in the determination of the long term dynamics of Zika in a population is the parameter K L which represents how well men is capable of sexually transmitting ZIKV after the viremic period ( figure 3), when compared to during it. It has been confirmed that some men can test positive for ZIKV RNA in the semen months after the viremic period 22,23 . Our model shows that until we can properly measure or estimate the sexual transmissibilities between humans in post-viremic stage, we must be prudent 24 and recommend protected sex to men returning from endemic areas with or without symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…However, it remains to be determined whether a ZIKV vaccine will need to achieve true sterilizing immunity to protect a pregnant woman and her fetus from congenital ZIKV syndrome, which could be a higher bar than protecting a non-pregnant adult against ZIKV viremia. A more detailed understanding of potential viral reservoirs, such as in semen, will also be needed (Atkinson et al, 2017; Matheron et al, 2016). …”
Section: Challenges Facing Clinical Development Of Zikv Vaccinesmentioning
confidence: 99%
“…During the outbreak in the French Polynesia, Polymerase Chain Reaction (PCR) positivity for ZIKV was found in 3% of the sera of blood donations [3]. Additionally, the virus can persist in vaginal secretions and semen for up to 115 days [17,[24][25][26][27].…”
Section: Transmissionmentioning
confidence: 99%